The Identity, Fungibility and Anonymity of Money. Issue 2 (25th December 2019) - Berg, Alastair
Abstract : The fungibility of money is a characteristic which contributes to the quality of money. Fungibleness is itself related to the technical ability to associate a unit of currency with its past instances of exchange. This history is analogous to the identity of money. The identity of an individual unit of exchange is increasingly important as cash becomes less common, and banks require more information about the provenance of money. Private currencies, including Bitcoin and Libra, are themselves subject to tracking. The prior financial – and potentially political – activities of a user determine the fungibility of the currency they hold. Different money technologies provide varied levels of privacy, while cryptocurrencies offer users the potential to choose the level of information they share.